Pharmaceutico- Analytical Study of Masha Taila - Bishnoi, Rakesh; Fiaz, Shamsa (International Research Journal of Ayurveda & Yoga, 2021)
Background – Masha Taila is an Ayurvedic formulation used for Urdhwajatrugata Vyadhi. Present study is attempted to develop some newer approaches for the quality control and standardization of Masha Taila. Material and methods - The present study was designed to standardize an Ayurveda formulation, Masha Taila, by evaluation of its organoleptic, physico-chemical and chromatographic parameters. Result- The organoleptic analysis of Masha Taila reveals its pale-yellow colour and characteristic odour. Physico-chemical study reveals Moisture content-0.25 %, Density-0.93018 gm/ml, Sp. Gravity 0.93297, Refractive index-1.3758, Total Fat Content -90.45%, Iodine value-2.07, Saponification value- 124.76, acid value- 1.288%, Peroxide value-4.134, Viscosity- 27.2245. In TLC, Rf values were found 0.98, 0.91, 0.41, 0.38, 0.25, 0.2 when visualized under iodine vapour. Conclusion – This study may aid as a reference for standardization and quality control analysis of Masha Taila in further researches.